Strategies For Improving Goods Transport Efficiency (Case Study PT. Bhanda Ghara Reksa, Persero) - Putu Diva Ariesthana Sadri; Putu Ayu Govika Krisna Dewi; AA Bagus Oka Krishna Surya (Politeknik Transportasi Sungai, Danau dan Penyeberangan Palembang, 2022)
Indonesia's Logistic Performance Index based on World Bank data in 2018 was ranked 46th out of 160 countries. Rating indicated logistics activities in Indonesia are not efficient and effective when viewed from the seven indicators. This research was conducted considering the importance of increasing the efficiency of the transportation of goods both in terms of speed of service time, travel costs, and the safety of the goods being transported to improve services to the community. This research is expected to contribute to the creation of efficiency in the transportation of goods. The economy and people's purchasing power in areas that are quite far apart from sources of production are increasing. The distribution of selling prices and people's purchasing power can be evenly distributed from Sabang to Merauke. Researchers investigate a case at PT. BGR Persero by using the interview method and SWOT analysis. The results of the study found that PT. BGR Persero is on the right track. The results of the SWOT analysis show the position of PT. BGR is in quadrant 1 (one). The strategy that is effectively implemented is an aggressive strategy, conducted by maintaining good conditions and expanding other types of businesses such as transporting dangerous goods and leasing warehouse assets.